Nabywanie nowych doświadczeń w życiu codziennym jednostki w postmonocentrycznym polskim ładzie społecznym = Acquiring new experiences in everyday life of an individual in the postmodernist social order in Poland - Radziewicz-Winnicki, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The author is primarily concerned with psychological and social dimensions of the transformational process in the context of contemporary changes in Poland.
Keywords: psychologia; socjologia; transformacja